Assessing the Impact of Recurrent Aphthous Ulcer on Oral Health-Related Quality of Life - Nishath S. Abdul (Journal of Pharmacy and Bioallied Sciences, 2025)
Introduction: Recurrent aphthous ulcer (RAU), commonly known as canker sores, is a prevalent oral mucosal disorder impacting approximately 20% of the general population. Despite their non-contagious nature, RAU significantly affects the Oral Health-Related Quality of Life (OHRQoL) owing to the painful and recurrent nature of the ulcers. Methods: Search was conducted across databases such as PubMed, Scopus, and Web of Science, focusing on articles using validated instruments such as the Oral Health Impact Profile to measure the impact of RAU on OHRQoL. A qualitative synthesis was performed to assess the relationship between RAU and dimensions of OHRQoL such as functional limitations, physical pain, psychological discomfort, and social disability. Results: The review highlighted that pain is the most significant factor diminishing OHRQoL in RAU patients. The recurrent nature of the ulcers also leads to considerable psychological and social challenges, including anxiety and social withdrawal, emphasizing the need for comprehensive management strategies. Conclusion: RAU profoundly affects various aspects of daily life, necessitating a multidimensional approach to management that addresses both the physical symptoms and psychological impacts. Effective treatment strategies, personalized to individual needs, are essential for improving the overall quality of life in affected individuals.